Pias3-dependent SUMOylation controls mammalian cone photoreceptor differentiation - Onishi, Akishi (2010)
Selective expression of retinal cone opsin genes is essential for color vision, but the mechanism mediating this process is poorly understood. Both vertebrate rod and medium wavelength-sensitive (M) cone photoreceptors differentiate by repression of a short wavelength-sensitive (S)-cone differentiation program. We show that Pias3 acts in mouse cone photoreceptors to activate expression of M-opsin and repress expression of S-opsin, with the transcription factors Trβ2 and Rxrγ mediating preferential expression of Pias3 in M-cones. Finally, we observe that Pias3 directly regulates M- and S-cone opsin expression by modulating the cone-enriched transcription factors Rxrγ Rorα, and Trβ1. This study reveals that Pias3-dependent SUMOylation of photoreceptor-specific transcription factors is a common mechanism that controls both rod and cone photoreceptor subtype specification, regulating distinct molecular targets in the two cell types.